Formulation, Development and Evalution of Surface Solid Dispersion of Larcandipine for Solubility and Dissolution Enhancement - Vaphare, Ashok M; Banerjee, DR.S K; Gadhave, M V; Gaikwad, DR.D D (Asian Journal of Pharmaceutical Research and Development, 2014)
The aim of †the present study was to improve lercanidipine HCl solubility and in vitro dissolution rate by preparing solid dispersion with using the solvent evaporation technique. Solid dispersions with Sodium starch glycolate (SSG), Crospovidone (CP) and Croscarmellose sodium (CCS) (as carriers) were prepared in drug: carrier (1:2, 1:4, 1:6, 1:8, and 1:10) ratios along with the corresponding physical mixtures. Analytical techniques, FT-IR spectroscopy, differential scanning calorimetry (DSC) and X-ray diffraction (XRD) were used to characterize the drug in the physical mixtures and solid dispersions. The solubility and wettability studies of solid dispersions as well as physical mixtures showed greater improvement compared to the pure drug. Higher in vitro dissolution of solid dispersions was recorded compared to their corresponding physical mixtures and the pure drug. Solid dispersion in 1:6 drug to carrier ratio exhibited the highest drug release (97 %) in comparison with solid dispersion in 1:6 drug to carrier ratio (97% drug release), whereas there was no significant improvement in dissolution of solid dispersion in drug to carrier ratio in comparison with its physical mixture. The FT-IR spectra suggested that there was no interaction between lercanidipine HCl and Methanol when prepared as a solid dispersion. No representative DSC peaks for drug were observed for solid dispersion indicating the transformation of crystalline structure of lercanidipine HCl. The absence of XRD peaks of the drug in solid dispersion demonstrated that drug was present in amorphous structure suggesting the transformation of crystalline form of lercanidipine HCl to amorphous form. This polymorphic transformation contributes to faster dissolution rate of solid. The dissolution efficiency values for pure drug and solid dispersion compared also support this aspect.